High-repetition-rate narrow pulse width mid-infrared optical parametric oscillator based on PPMgLN crystal. (23rd December 2015) - Wang, Zi-Jian; Yu, Yong-Ji; Zhai, Rui-Zhi; Chen, Xin-Yu; Wu, Chun-Ting; Jin, Guang-Yong
Abstract: This paper reports a narrow pulse width optical parametric oscillator (OPO) based on periodically poled MgO:LiNbO3 (PPMgLN). When the maximum pumping power of the 1064 nm laser was 26.07 W, the acousto-optical (AO) Q-switch repetition rate was 70 kHz and the PPMgLN crystal grating period was 29 μ m; a 3840 nm mid-infrared light output power of 4.86 W was obtained at 150 °C, corresponding to a pulse width of 9.56 ns. The optical–optical conversion efficiency was about 18.6%. In addition, by changing the temperature between 25 °C to 200 °C, a tunable mid-infrared wavelength of 3765–3974 nm output laser was achieved.